Preliminary Observations on the Behavior and Ecology of the Peruvian Night Monkey (Aotus Miconax: Primates) in a Remnant Cloud Forest Patch, North Eastern Peru. (March 2013) - Shanee, Sam; Allgas, Nestor; Shanee, Noga
The Peruvian night monkey ( Aotus miconax ) is endemic to the eastern slopes of the Andes in northern Peru. We present preliminary behavioral data on A. miconax collected during 12 months of surveys on a single group living in a 1.4 ha forest fragment near the Centro Poblado La Esperanza, Amazonas Department. Follows were conducted for five nights each month around full moon. The group used 1.23 ha as their home range. Night ranges were between 0.16 and 0.63 ha. Activity budgets were 32 % feeding, 53 % travelling and 13 % resting. Average night path length was 823 m and average travel speed was 117 m/h. The study group has one of the smallest home ranges recorded for a night monkey group, probably the result of its isolated habitat. These results represent the first behavioral data on this species but results are limited by small sample sizes. A. miconax remains one of the least studied of all primates and is threatened by continued expansion of human populations and hunting.